ACT strategy smart / Kelly C Roell - Roell, Kelly C.
ACE the ACT with ACT Strategy Smart The ACT Strategy Smart test prep is designed to help college-bound students raise their score on the ACT and get into the college of their dreams. Authored by About.com's test prep specialist, ACT Strategy Smart gives you crucial test-taking strategies you need to know before exam day. By learning these effective techniques, you can master the ACT and get a higher score. Written in a student-friendly, easy-to-understand style, the author focuses on the content of the ACT, explains the concepts tested in each section of the test, and offers strategies, tips, and pointers on how to answer questions correctly. Practice drills and exercises reinforce what you have learned and identify the areas where you need extra study. Divided into four weekly study sessions, each week covers the unique strategies you need to score high on the English, Math, Science, and Reading portions of the exam. An optional fifth week leads you through strategies for taking the ACT Writing Test.